The role of Andaluzian poetry in the formation and development of the lyrics of the Provencal troubadours - ВЕЛИЧКО, М.; БРАТЕЛЬ, О. (Київський національний університет імені Тараса Шевченка, 2020)
In the review article the theories of the Arabic origin of West European chivalrous poetry were analyzed. The article deals with the problem of the direct interaction between Arabic and European literary traditions, in particular, the probability of the impact of the Arab-Spanish strophic poetry on Provencal troubadour's lyrics and the possibility of the influence of Andalusian poetry on Spanish and Provencal. So that it is established that al-Andalus was a multilingual society in which the Andalusi Romance dialects were spoken and written alongside Arabic. In Europe, and from scholars working in departments of modern national languages, this usually means the discussion of what it means to write in Middle English, or German, or French instead of Latin. The Andalusian poets could easily convey in Romance the motives and themes inherent in Arabic classical literature, and with the help of the Arabic language they expressed elements of Roman folk poetry. The analysis of various researches showed that the issue of the historical and geographical formation and development of Arab-Spanish poetry during the Middle Ages were studied by Arab and European sceintists of past centuries, as well as by the modern literary scientists. Modern studies of the Arab-Spanish medieval stanza do not deny the existence of an interaction between European and Arabic lyrics, but the role of this interaction on the scale of the history of world literature remains unclear. Lyrics of the troubadours of the 11th–14th centuries was a unique synthesis of many literary elements of church Latin poetry, folk poetry and Arab influences, and strongly influenced on the history of Italian, Spanish, English, Portuguese, German literature.

Проведено оглядовий аналіз тези про арабське походження західноєвропейської лицарської лірики. Порушено питання безпосередньої взаємодії європейської та арабської літературних традицій, зокрема ймовірного впливу арабо-іспанської строфіки на лірику провансальських трубадурів як представників літературної школи, звідки бере свій початок традиція новоєвропейської лірики. Продемонстровано результати контактування середньовічних арабської та європейської літератур на прикладі впливу андалузької поезії на іспанську й провансальську. З'ясовано, що безсумнівним для науковців є факт багатомовності андалузького суспільства, у якому паралельно функціонували романські говірки і класична арабська мова. У європейських розвідках, особливо в працях науковців, присвячених національним мовам, дослідження питання зводиться до шляхів творення поезії середньовічним варіантом майбутніх європейських мов, а не латиною. Андалузькі поети з легкістю могли передати мотиви й тематику, притаманні арабській класичній літературі, за допомогою романської мови, а до арабської мови звертатися для вираження елементів народної романської лірики. Аналіз досліджень і публікацій показав, що питання історико-географічного становлення та розвитку арабо-іспанської поезії в період Середньовіччя розглядали арабські та європейські вчені минулих століть, а також сучасні літературознавці. Останні дослідження арабо-іспанської середньовічної строфіки не заперечують існування взаємодії між європейською і арабською лірикою, проте досі не визначеною залишається роль цієї взаємодії в масштабі історії світової літератури. Лірика трубадурів XI–XIV ст. була унікальним синтезом багатьох літературних елементів церковної поезії, фольклору, а також арабських впливів. Вона виявилася вирішальним чинником в історії становлення італійської, іспанської, англійської, португальської, німецької літератур.
Роль андалузької поезії у процесі становлення та розвитку лірики провансальських трубадурів
Keywords: провансальські трубадури; арабо-іспанська поезія; строфічна поезія; андалузька строфіка; арабо-іспанська поезія; Provencal troubadours; Arab-Spanish poetry; strophic poetry; Andalusian stanza; Arab-Spanish poetry